Effects of Insuline on Oxidative Stress and Free Fatty Acid Level in Left Ventricular Muscles of Diabetic Rats - Kavak, Servet; Ayaz, Lokman; Emre, Mustafa; Bozkurt, Abdi (Asian Journal of Chemistry, 2010)
Studies were carried out to examine and compare the effects of streptozotocin-diabetes on 3-nitrotyrosine (3-NT), Malondialdhyde (MDA) and lipid profiles related parameters in the heart from male rats. Effects of insulin (INS) treatment were also evaluated. The diabetic state severely compromised the 3-NT, MDA and lipid profiles defense mechanism in the left ventricular muscle tissue and the effects were more pronounced in the male rats. Wistar albino male rats were randomly divided into an untreated control group (C), a diabetic group (D) that was treated with a single intraperitoneal injection of streptozotocin (STZ) (45 mg kg-1), D + INS group which were treated with INS one times a day by injection subcutaneous, respectively. Lipid profiles, HbA1c and blood glucose levels in the circulation and MDA and 3-NT levels in left ventricular muscle were measured. Treatment of diabetic rats with INS resulted in a time-dependent decrease in blood glucose. It is found that the lipid profile and HbA1c levels in D + INS group reached the untreated control group rat values at the end of the treatment period. It is found that the lipid profile and HbA1c levels in D + INS group reached the C rat values at the end of the treatment period. In group D, 3-NT and MDA levels were found to be increased when compared with C and D + INS groups. In the D + INS group, MDA levels were found to be decreased when compared with untreated control group. This study shows a direct correlation between hyperglycemia and the production of MDA and nitrotyrosine, a marker of oxidative stress, in diabetic rat left ventricular muscle.